The relevance of a right scale for sampling when studying high-resolution behavioral dynamics - Barberis, Lucas (2023)
Fil: Barberis, Lucas. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía Física y Computación; Argentina.